Synergistic effects of surface-enhanced Raman spectroscopy and enzyme-linked immunoassays in diagnosis of Alzheimer's disease, mild cognitive impairment, and late-life depression - Xi Mei; Xi Mei; Zheng Zhao; Zheng Zhao; Juan Wang; Juan Wang; Conglong Qiu; Longhui Li; Longhui Li; Changchun Xiong; Shanshan Zhu; Chengying Zheng (Frontiers in Neurology)
BackgroundObjective tests that can be used to identify neurodegenerative diseases and neuropsychiatric disorders are urgently needed. The primary objective of this study is to evaluate the diagnostic accuracy of surface-enhanced Raman spectroscopy (SERS), a novel blood-based detection method, in differentiating neurodegenerative diseases and neuropsychiatric disorders. Additionally, we aim to assess the synergistic diagnostic performance of combining SERS with enzyme-linked immunosorbent assay (ELISA) technology for Alzheimer's disease (AD), mild cognitive impairment (MCI), and late-life depression (LLD).MethodsIn total, 23 patients with AD, 24 with MCI, 20 with LLD, and 20 cognitively normal (control) individuals were enrolled. ELISA and SERS were used to test various biomarkers in the AD, MCI, LLD, and control groups.ResultsAmyloid-β, tau, brain-derived neurotrophic factor, proinflammatory cytokine IL-1β, and growth differentiation factor-15 levels as measured using ELISA significantly differed among the four groups (P < 0.05). SERS peaks at 592 (P = 0.038), 725 (P = 0.001), 1,003 (P = 0.010), 1,331 (P = 0.000), and 165 cm−1 (P = 0.000) likewise significantly differed among the four groups. The area under the curve was significantly higher after combining multiple blood indicators than that with single-blood indicators.ConclusionsCombining SERS and ELISA can significantly increase diagnostic accuracy for AD, MCI, and LLD. The findings are expected to provide potential therapeutic targets for precise intervention in these diseases, thereby contributing to improved clinical stratification and personalized treatment strategies.Clinical trial registry numberChiCTR2300076307 (30/09/2023).